New Model of Anti Radicalisme Learning for Moslem Teacher - Saputra, Ucok Agus (International Conference of Moslem Society, 2016)
Post-fall of the New Order regime, the action of Islamic radicalism spreads out fast in Indonesia. Unluckily, actors and the perpetrators are mostly Muslimand claiming graduated from Islamic educational institutions. Radical Islamic movements nowadays are worrying the people and threaten the life of the nation that contains the values of pluralism, tolerance, and acculturative, including in religion. According to way of life on Indonesian, Pancasila, and the 1945 Constitution and the Republic of Indonesia which is the basics of nation and state are also threatened. even their movement tends to do with violence. Proven by the presence of several violent incidents that resulted in deaths were not counted. (National Agency for Counter of Terrorism, 28/8/2002). Therefore, Indonesia (and even the world) needs strategies to prevent the anti-radicalism and terrorism. Learning the last fact, education that be designed by conforming new model of learning for Moslem Teacher is absolutely needed. The approach to the handle the Islamic radicalism must always be strived, One of models is through character education. Education is partly done by reconstructing the Islamic Religious Education (PAI) that is taught in educational institutions. Reconstruction of PAI should be able to produce learners that possess attitude of tolerant, moderate and inclusive. In short, there is a tendency of systematic efforts made by certain religious groups to teach the doctrine of religious hardliners among students of Elementary School (SD), that often reborn radicalization. Here, the writer will show how Moslem teacher can take anti-radicalims learing by some new models that can be implemented, namely the de-radicalization preventive, de-radicalization preservative against moderate Islam, and curative deradicalised.